2000
DOI: 10.1007/s004180000224
|View full text |Cite
|
Sign up to set email alerts
|

Tumor structure and extracellular matrix as a possible barrier for therapeutic approaches using immune cells or adenoviruses in colorectal cancer

Abstract: In this article we report about the role that tumor structure and extracellular matrix (ECM) may play in immunotherapy and in gene therapy using adenoviruses. We performed studies in a rat model for colorectal cancer, CC531, and in specimens of human colorectal cancer. The tumors were composed of two compartments, tumor cell nests surrounded by stromal cells. ECM proteins were expressed in the stromal part, where the blood vessels were also located. Furthermore, in several tumors, the tumor cell nests were sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 20 publications
3
33
0
Order By: Relevance
“…[42][43][44] However, ultrastructural studies showed that NK cells display a marked ability to alter their shape, thus facilitating their extravasation and intratumor migration. 45,46 This would question the extracellular matrix proteins as a true physical barrier.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44] However, ultrastructural studies showed that NK cells display a marked ability to alter their shape, thus facilitating their extravasation and intratumor migration. 45,46 This would question the extracellular matrix proteins as a true physical barrier.…”
Section: Discussionmentioning
confidence: 99%
“…This can best be explained by inefficient dispersion of the CRAd through the tumor mass after intratumoral injection. Barriers within the established tumor, such as connective tissue and tumor matrix, may limit the spread of virus (34). In OS, osteoid calcification could be such a hurdle for viral therapy that needs to be overcome.…”
Section: Discussionmentioning
confidence: 99%
“…At early time points of adhesion and spreading of colon carcinoma cells in vitro, the epidermal growth factor through phosphorylation of focal adhesion kinase induced activation of 2 1 integrin and furthermore organization of the actin cytoskeleton involved in lamellipodia formation. In a rat model of colorectal cancer, evidence was obtained that the ECM may constitute a barrier for both immune cells and adenoviruses in tumor therapy (Kuppen et al 2001).…”
Section: Cell Adhesion Molecules and Extracellular Matrix Componentsmentioning
confidence: 99%